Pelatihan Mendesain Model Pembelajaran Problem Based Learning Di Sekolah Dasar Kota Bandar Lampung - Herpratiwi; Yulianti, Dwi; Nurwahidin, Muhammad; Tohir , Ahmad; Arrasyid, Abi Krisna (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2024)
Based on the initial study of primary school educators in the City of Bandar Lampung, it was found that in designing learning processes, educators have not yet applied systematic thinking principles. Most educators tend to imitate or create their own lesson plans without relying on valid research. Therefore, training on lesson design is highly necessary. This community service programme aims to address the issue of low professional and pedagogical competence among primary school teachers, particularly in designing lesson plans. The implementation of the service comprises several stages: (1) drafting the training design and instruments, (2) expert validation through an FGD for the training design and instruments, (3) carrying out stage I, which includes a pre-test followed by training, (4) conducting stage II, which involves testing the learning tools developed by the teachers, and (5) a post-test to assess the participants' final competence. The methods used include expository teaching, question and answer sessions, group work, and presentations. The sample of primary school teachers was selected randomly using area random sampling techniques, utilising instruments such as observation, tests, and structured interviews. The training results indicated a significant improvement, with pre-test scores of 25% rising to 75% in the post-test, reflecting a 50% increase.